Comparative analysis of extraction methods for bioactive compounds in aromatic and medicinal plants (Agroindustrial Science, 2025)
The main extraction techniques for bioactive compounds from aromatic and medicinal plants include maceration, distillation, supercritical CO2, and ultrasound. These methods can be differentiated based on their efficiency, sustainability, and their ability to extract and preserve compounds such as essential oils, which primarily contain flavonoids and terpenes. Traditional methods, such as maceration and distillation, are useful for extracting heat-sensitive and volatile compounds but have limitations in terms of time and energy consumption. In contrast, modern techniques, such as supercritical CO2 and ultrasound, are more efficient and environmentally friendly, enhancing compound preservation and significantly reducing environmental impact; however, they are more costly than the other methods. Nevertheless, recent research has shown a significant increase in studies on supercritical CO2 and ultrasound, along with their growing adoption in industries such as cosmetics, food, pharmaceuticals, and biotechnology.